Sodium ion positive electrode material, positive electrode slurry, preparation method of positive electrode slurry, positive electrode plate and secondary battery
By designing a double-layer protective layer on the positive electrode material of sodium ion battery, the instability problem of the positive electrode material of sodium ion battery in the water environment is solved by using the water homogenization process, and efficient and environmentally friendly sodium ion battery production is achieved, improving the service life and performance of the battery.
Patent Information
- Application Number
- CN202411901298.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-23
AI Technical Summary
The existing sodium ion battery positive electrode materials are unstable in the water environment, resulting in structural distortion and rapid attenuation of battery capacity. The traditional oil-based homogenization process is costly and has serious environmental pollution, and there is a lack of high-efficiency sodium ion positive electrode materials and processes suitable for water-based homogenization systems.
The sodium ion positive electrode material is used for a double-layer protective layer. The first cladding layer consists of an organic material having a hydrophobic molecular framework and at least two anionic head groups. The second cladding layer reacts with the organic material through a water-soluble salt to form a precipitated protective layer, which is suitable for water-based homogenization process.
The stability of sodium ion positive electrode material is improved, so that it can show excellent electrochemical performance in the aqueous homogenization system, and its long cycle stability and rate performance are comparable to that of the oil homogenization process, while reducing production costs and reducing environmental pollution.
Smart Images

Figure CN119725449A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and in particular to a sodium ion positive electrode material, a positive electrode slurry, a preparation method thereof, a positive electrode sheet and a secondary battery. Background Art
[0002] Since lithium-ion batteries were commercialized by Sony in 1991, they have achieved great success in applications such as portable electronics, electric vehicles, and smart grids. However, the scarcity and uneven distribution of lithium resources in nature have caused the cost of lithium-ion batteries to rise year by year. At the same time, the sustainable development of lithium resources has also become a focus of attention. Sodium has similar physical and chemical properties to lithium. In addition, sodium has the characteristics of abundant resources, uniform distribution, and low extraction cost. Therefore, sodium-ion batteries are regarded as a beneficial supplement to lithium-ion batteries, and have shown broad application prospects in the field of large-scale energy storage in recent years.
[0003] Due to the corrosive effect of the water environment on the positive electrode material of the sodium ion battery, the active sodium ions inside the material are constantly released, which in turn causes serious distortion of the internal structure of the material and rapid decay of the battery capacity.
[0004] In view of this, the preparation process of sodium-ion battery positive electrode sheets that are sensitive to moisture generally adopts oil-based slurry technology. The current mainstream system is the polyvinylidene fluoride (PVDF) binder / N-methylpyrrolidone (NMP) solvent system. However, the high-boiling point and toxic solvent NMP used in large quantities in this process will cause the energy consumption of solvent recovery to be as high as 46% of the total energy consumption, while the manufacturing cost of coating and drying links accounts for about 20% of the total cost. These data show that the traditional oil-based slurry process not only leads to high preparation costs and energy consumption, but the large amount of organic solvents used also causes serious pollution to the environment.
[0005] If the sodium-ion battery positive electrode material itself and the slurry process can be finely modified and optimized, while ensuring that the sodium-ion battery positive electrode material maintains excellent electrochemical activity, the water-based slurry process can successfully replace the traditional oil-based slurry process. This will significantly reduce the production cost of sodium-ion batteries and promote the preparation process to move towards a green and environmentally friendly direction.
[0006] Researchers have tried to propose strategies to optimize positive electrode materials, such as element doping and surface coating. At the same time, by precisely controlling the pH value of the aqueous slurry, shortening the homogenization time, and increasing the solid content, efforts are made to achieve the stability of the positive electrode materials of sodium-ion batteries in the aqueous phase. However, compared with the electrodes prepared by the oil-based slurry process, the positive electrode electrodes prepared by the aqueous homogenization process still have a certain gap in electrochemical performance. More importantly, the current solution lacks universality and is difficult to apply to layered positive electrode oxides for sodium-ion batteries. In view of this, there is an urgent need to solve the problem of the stability of positive electrode materials for sodium-ion batteries in the aqueous phase from the two aspects of material modification and process optimization.
[0007] There is no mature and effective sodium ion positive electrode material and homogenization process suitable for aqueous homogenization system in the prior art. Therefore, how to develop a sodium ion positive electrode material and aqueous homogenization process suitable for aqueous homogenization system has become a problem that needs to be solved urgently. Summary of the invention
[0008] In order to solve the above technical problems, the purpose of the present invention is to provide a sodium ion positive electrode material, a positive electrode slurry and a preparation method thereof, a positive electrode sheet and a secondary battery. The sodium ion positive electrode material of the present invention has a double protective layer, which improves the stability of the sodium ion positive electrode material itself, can be applied to an aqueous slurry system, and the prepared secondary battery has excellent long-cycle stability, which can be comparable to the performance of the positive electrode material obtained by an oil-based slurry system.
[0009] To achieve this object, the present invention adopts the following technical solutions:
[0010] In a first aspect, the present invention provides a sodium ion positive electrode material, the sodium ion positive electrode material comprising a sodium ion positive electrode material core, a first coating layer coated on the surface of the sodium ion positive electrode material core, and a second coating layer coated outside the first coating layer;
[0011] The raw material of the first coating layer includes an organic material having a hydrophobic molecular skeleton and at least two anionic head groups;
[0012] The second coating layer includes a precipitation product of a reaction between an anionic head group in an organic material and a water-soluble salt.
[0013] The "anionic head group" of the present invention refers to a negatively charged functional group connected to the main chain or long chain structure in the organic molecular structure. The functional group can be, for example, a carboxylate (-COO - ), thiol (-SH), sulfonate (-SO3 - ), sulfate (-OSO3 - ) or phosphate (-PO4 3- )wait.
[0014] In the sodium ion positive electrode material provided by the present invention, the organic material coating layer contained therein can play an auxiliary hydrophobic role on the one hand, and on the other hand, it has at least two anion head groups, wherein the anion head group on one side can be anchored on the surface of the positive electrode material, and the anion head group on the other side can react with a water-soluble salt additive to generate a precipitation protective layer, and the generated precipitation protective layer can further improve the hydrophobic ability while also having a higher ionic conductivity, thereby ensuring the stability of the electrochemical performance of the sodium ion positive electrode material.
[0015] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0016] Preferably, the thickness of the first coating layer is 2nm-10nm, for example, 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm or 10nm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0017] Preferably, the thickness of the second coating layer is 2nm-10nm, for example, it can be 2nm, 2.5nm, 3nm, 3.5nm, 4nm, 4.5nm, 5nm, 5.5nm, 6nm, 6.5nm, 7nm, 7.5nm, 8nm, 8.5nm, 9nm, 9.5nm or 10nm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0018] Preferably, the organic material comprises any one or a combination of at least two of 1,5-naphthalene disulfonic acid, 1,3,5-naphthalene trisulfonic acid, 1,3,6-naphthalene trisulfonic acid, 1,3,7-naphthalene trisulfonic acid, 1,3,6,8-pyrene tetrasulfonic acid, 1,4-phenylenediphosphonic acid, 1,4-butane disulfonic acid, 12-mercaptododecyl phosphoric acid, 1,5-pentane diphosphoric acid or 1,12-dodecane diphosphoric acid. Typical but non-limiting combinations include a combination of 1,5-naphthalene disulfonic acid and 1,3,5-naphthalene trisulfonic acid, a combination of 1,3,6-naphthalene trisulfonic acid and 1,3,6,8-pyrene tetrasulfonic acid. a combination of 8-pyrenetetrasulfonic acid, a combination of 1,4-benzenediphosphonic acid and 1,4-butanediphosphonic acid, a combination of 12-mercaptododecylphosphonic acid and 1,5-pentanebisphosphonic acid, a combination of 1,5-naphthalenedisulfonic acid, 1,3,5-naphthalenetrisulfonic acid, 1,3,6-naphthalenetrisulfonic acid, 1,3,7-naphthalenetrisulfonic acid and 1,3,6,8-pyrenetetrasulfonic acid, a combination of 1,4-butanedisulfonic acid and 1,5-pentanebisphosphonic acid or 1,12-dodecanebisphosphonic acid, or a combination of 1,5-naphthalenedisulfonic acid, 1,3,5-naphthalenetrisulfonic acid and 1,3,6,8-pyrenetetrasulfonic acid.
[0019] On the one hand, the present invention uses an organic material with a long carbon chain (C>5) to achieve stronger hydrophobicity and improve the stability of the sodium ion positive electrode material to water. On the other hand, the organic material in the present invention contains at least two anion head groups, one of which is used as an anchoring group to link the organic molecule to the surface of the positive electrode material, and the other part of the group can react with a water-soluble salt additive to form a precipitation protective layer with strong ion conductivity.
[0020] Preferably, the precipitated product in the second coating layer comprises any one or a combination of at least two of a barium salt, a magnesium salt, a calcium salt or a zinc salt, typical but non-limiting combinations include a combination of a barium salt and a magnesium salt, a combination of a calcium salt and a zinc salt, a combination of a barium salt and a calcium salt, a combination of a barium salt, a magnesium salt and a calcium salt, a combination of a barium salt, a calcium salt and a zinc salt, and a combination of a magnesium salt, a calcium salt and a zinc salt.
[0021] In a second aspect, the present invention provides a method for preparing the sodium ion positive electrode material according to the first aspect, the method for preparing the sodium ion positive electrode material comprising the following steps:
[0022] Coating an organic material on the surface of a sodium ion positive electrode material by a liquid phase method and / or a gas phase method to prepare a sodium ion positive electrode material containing a first coating layer;
[0023] The sodium ion positive electrode material containing the first coating layer, a conductive agent, a binder, a water-soluble salt additive and water are mixed, and the sodium ion positive electrode material is obtained through reaction and separation.
[0024] In a third aspect, the present invention provides a positive electrode slurry, wherein the positive electrode slurry comprises the sodium ion positive electrode material as described in the first aspect.
[0025] The positive electrode slurry provided by the present invention can greatly reduce pollution to the environment and reduce costs by using cheap, non-toxic and pollution-free water as a solvent.
[0026] In a fourth aspect, the present invention provides a method for preparing the positive electrode slurry as described in the second aspect, the preparation method comprising the following steps:
[0027] Coating an organic material on the surface of a sodium ion positive electrode material by a liquid phase method and / or a gas phase method to prepare a sodium ion positive electrode material containing a first coating layer;
[0028] The sodium ion positive electrode material containing the first coating layer, a water-soluble salt additive and water are mixed to obtain the positive electrode slurry through a first reaction.
[0029] The present invention uses water as a solvent in the homogenization process to reduce production costs. At the same time, by adding a water-soluble salt additive into the slurry, the water-soluble salt additive and the organic material in the sodium ion positive electrode material containing the first coating layer spontaneously undergo a double decomposition reaction, and a precipitation protection layer, an artificial solid electrolyte interface layer (CEI), is generated on the surface of the sodium ion positive electrode material. This not only ensures the stability of the sodium ion positive electrode material to water, but also improves the ionic conductivity of the coating layer, maintains the structural stability of the sodium ion positive electrode material during long-term circulation, and improves the service life of the sodium ion battery.
[0030] The water-based slurrying process adopted in the present invention has a simple and efficient operating procedure and is widely applicable. In addition, the organic solvents used in the traditional homogenization process are abandoned, which not only greatly reduces the preparation cost of sodium ion batteries and is more in line with industrialization needs, but also enhances the environmental friendliness of the production process.
[0031] Preferably, the mass ratio of the sodium ion positive electrode material and the water-soluble salt additive of the first coating layer is 1:(0.01-0.3), for example, it can be 1:0.01, 1:0.02, 1:0.03, 1:0.04, 1:0.05, 1:0.06, 1:0.07, 1:0.08, 1:0.09, 1:0.1, 1:0.15, 1:0.2, 1:0.25 or 1:0.3, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0032] The present invention further controls the mass ratio of the sodium ion positive electrode material and the water-soluble salt additive of the first coating layer to be 1:(0.01-0.3) to ensure that a complete precipitation protection layer is formed on the surface of the first coating layer of the sodium ion positive electrode material. While ensuring the water stability of the positive electrode material, it can have a higher ionic conductivity. The content of the additive will have a significant impact on the electrochemical performance of the electrode after subsequent water homogenization. When the additive content is too little, the generated precipitation layer cannot completely cover the surface of the positive electrode material. The hydrophobic performance of the precipitate is greatly reduced, resulting in the gram capacity of the electrode being significantly lower than that of the oil-based homogenate; when the additive content is too much, the precipitation layer is too thick, which will also affect the electrode during the cycle. + The migration of the electrolyte results in the gram capacity and rate performance being significantly lower than that of the oil-based stirred slurry electrode.
[0033] Preferably, the water-soluble salt additive includes any one of a soluble barium salt, a soluble magnesium salt, a soluble calcium salt or a soluble zinc salt, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of a soluble barium salt and a soluble magnesium salt, a combination of a soluble calcium salt and a soluble zinc salt, a combination of a soluble magnesium salt and a soluble calcium salt, a combination of a soluble barium salt, a soluble calcium salt and a soluble zinc salt, a combination of a soluble barium salt, a soluble magnesium salt and a soluble calcium salt, and a combination of a soluble barium salt, a soluble magnesium salt, a soluble calcium salt and a soluble zinc salt.
[0034] The present invention does not specifically limit the type of sodium ion positive electrode material, including but not limited to any one or a combination of at least two of layered oxide, Prussian blue or polyanion positive electrode materials.
[0035] The present invention does not specifically limit the type of the conductive agent, including but not limited to any one of acetylene black, carbon fiber, carbon nanotube, conductive graphite, Super P or graphene, or a combination of at least two thereof.
[0036] The binder in the present invention is a water-soluble binder, which is a stable suspension formed by dispersing a polymer or resin in water. The present invention does not specifically limit the type of the water-soluble binder, including but not limited to any one of polyacrylic acid, sodium polymethacrylate, sodium alginate, sodium carboxymethyl cellulose, xanthan gum or guar gum, or a combination of at least two of them.
[0037] Preferably, the method for preparing the sodium ion positive electrode material containing the first coating layer comprises:
[0038] The sodium ion positive electrode material containing a first coating layer is prepared by coating the surface of the sodium ion positive electrode material with an organic material by a liquid phase method and / or a gas phase method.
[0039] The present invention uses molecular self-assembly technology to modify an ultra-thin, uniform, and dense molecular coating layer, which can stabilize the positive electrode material of the sodium ion battery in the aqueous slurry while maintaining good dispersibility.
[0040] Preferably, the steps of the liquid phase method include: mixing the sodium ion positive electrode material, the organic material and the first solvent, and performing a second reaction to obtain the sodium ion positive electrode material containing the first coating layer.
[0041] Preferably, the mass ratio of the sodium ion positive electrode material to the organic material is 1:(0.1-1), for example, it can be 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9 or 1:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0042] The present invention further controls the mass ratio of the sodium ion positive electrode material to the organic material to be 1: (0.1-1) to achieve the integrity of the first coating layer, so as to achieve the auxiliary hydrophobic effect. If the mass of the organic material is too small, the organic molecule coating is uneven and dense, resulting in poor stability of the positive electrode material in the water phase, and ultimately causing the gram capacity of the electrode to be lower than that of the oil-based homogenous electrode; if the mass of the organic material is too large, the organic molecule coating layer is too thick, which affects the Na + The embedding / detachment of the electrode leads to the rate performance and gram capacity being lower than that of the oil-based homogenous electrode.
[0043] Preferably, the first solvent comprises any one of tetrahydrofuran, ethanol or acetone or a combination of at least two thereof, typical but non-limiting combinations comprising a combination of tetrahydrofuran and ethanol, a combination of tetrahydrofuran and acetone, a combination of ethanol and acetone, a combination of tetrahydrofuran, ethanol and acetone.
[0044] Preferably, the second reaction further comprises solid-liquid separation, washing and drying.
[0045] Preferably, the gas phase method comprises: heating the organic material to deposit the volatilized organic material on the surface of the sodium ion positive electrode material to form a first coating layer, repeating the deposition and coating 2 to 4 times to obtain the sodium ion positive electrode material containing the first coating layer.
[0046] Preferably, the heating temperature is 100°C-150°C, for example, it can be 100°C, 110°C, 120°C, 130°C, 140°C or 150°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0047] Preferably, the heating time is 4h-8h, for example, it can be 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h, 7.5h or 8h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0048] As a preferred technical solution of the preparation method of the present invention, the preparation method comprises the following steps:
[0049] (1) mixing a sodium ion positive electrode material, an organic material, and a first solvent, and performing a second reaction to obtain a sodium ion positive electrode material containing a first coating layer;
[0050] Alternatively, the organic material is heated at 100° C. to 150° C. for 4 h to 8 h, so that the volatilized organic material is deposited on the surface of the sodium ion positive electrode material to form a first coating layer, and the deposition and coating are repeated 2 to 4 times to obtain a sodium ion positive electrode material containing the first coating layer;
[0051] (2) Mixing a sodium ion positive electrode material containing a first coating layer, a binder, a conductive agent, a water-soluble salt additive and water to obtain the positive electrode slurry through a first reaction.
[0052] In a fifth aspect, the present invention provides a positive electrode plate, wherein the positive electrode plate is prepared using the positive electrode slurry as described in the second aspect.
[0053] The positive electrode sheet provided by the present invention has lower preparation cost and has stable chemical and electrochemical properties.
[0054] In a sixth aspect, the present invention provides a secondary battery, comprising the positive electrode sheet as described in the fifth aspect.
[0055] The secondary battery prepared by the water-based slurry mixing process of the present invention has excellent cycle performance and rate performance, which is comparable to the oil-based slurry mixing process and far exceeds the existing technology, reduces the preparation cost of the sodium ion battery, and is more environmentally friendly.
[0056] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0057] Compared with the prior art, the present invention has at least the following beneficial effects:
[0058] (1) In the sodium ion positive electrode material provided by the present invention, the organic material coating layer contained therein can play an auxiliary hydrophobic role on the one hand, and on the other hand, it has at least two anion head groups, wherein the anion head group on one side can be anchored on the surface of the positive electrode material, and the anion head group on the other side can react with the water-soluble salt additive to form a precipitation protective layer. The generated precipitation protective layer can further improve the hydrophobic ability while also having a higher ionic conductivity, thereby ensuring the stability of the electrochemical performance of the sodium ion positive electrode material.
[0059] (2) The present invention provides an aqueous homogenization method, which can greatly reduce environmental pollution and reduce costs by using cheap, non-toxic and pollution-free water as a solvent. Water is used as a solvent in the homogenization process to reduce production costs. At the same time, by adding a water-soluble salt additive to the slurry, the water-soluble salt additive and the organic material in the sodium ion positive electrode material containing the first coating layer spontaneously undergo a double decomposition reaction, and a precipitation protective layer - an artificial solid electrolyte interface layer (CEI) is generated on the surface of the sodium ion positive electrode material, which not only ensures the stability of the sodium ion positive electrode material to water, but also improves the ionic conductivity of the coating layer, maintains the structural stability of the sodium ion positive electrode material during long-term circulation, and improves the service life of the sodium ion battery.
[0060] (3) The secondary battery prepared by the water-based slurry mixing process of the present invention has excellent cycle performance and rate performance, which is comparable to the oil-based slurry mixing process and far exceeds the existing technology. It not only greatly reduces the preparation cost of sodium ion batteries and is more in line with industrialization needs, but also enhances the environmental friendliness of the production process. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] Figure 1 This is a TEM image of the sodium ion positive electrode material containing the first coating layer prepared in Example 1 of the present invention;
[0062] Figure 2 Schematic diagram of the structure of the sodium ion positive electrode material containing the first coating layer and the second coating layer prepared in Example 1 of the present invention, 1-second coating layer, 2-first coating layer, 3-core of the sodium ion positive electrode material;
[0063] Figure 3 (a) TEM Mapping schematic diagram and (b) linear scanning diagram of the sodium ion positive electrode material prepared in Example 1 of the present invention;
[0064] Figure 4 It is a long cycle diagram of the sodium ion positive electrode material prepared by Example 1, Comparative Example 1 and Comparative Example 2 of the present invention;
[0065] Figure 5 This is the first cycle charge and discharge curve of the sodium ion positive electrode material prepared in Example 1 of the present invention;
[0066] Figure 6 This is the first cycle charge and discharge curve of the sodium ion positive electrode material prepared in Comparative Example 2 of the present invention;
[0067] Figure 7 This is the first cycle charge and discharge curve of the sodium ion positive electrode material prepared in Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0068] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.
[0069] In the following examples and comparative examples, unless otherwise specified, all reagents and consumables were purchased from conventional reagent manufacturers in the field; unless otherwise specified, the experimental methods and technical means used were conventional methods and means in the field.
[0070] Example 1
[0071] This embodiment provides a sodium ion positive electrode material and a method for preparing a sodium ion positive electrode slurry, the preparation method comprising the following steps:
[0072] (1) Mixed NaNi 0.33 Fe 0.33 Mn 0.33 O2 positive electrode material (commercially available), 1,5-naphthalene disulfonic acid (NTDS), and tetrahydrofuran (THF) solvent were stirred and dissolved, and heated in a water bath at 60°C for 6 hours to deposit the organic material on the surface of the sodium ion positive electrode material to form a first coating layer. After heating, the mixed solution was filtered after cooling to room temperature. The solid substance obtained was washed 3 times with THF solvent and dried to obtain NaNi containing the first coating layer. 0.33 Fe 0.33 Mn 0.33 O2 sodium ion positive electrode material; among them, NaNi 0.33 Fe 0.33 Mn 0.33 The mass ratio of O2 positive electrode material and 1,5-naphthalene disulfonic acid (NTDS) is 1:0.1.
[0073] (2) Mixed NaNi containing the first coating layer 0.33 Fe 0.33 Mn 0.33 O2 sodium ion positive electrode material, polyacrylic acid, acetylene black, BaCl2 additive and water, and the positive electrode slurry is obtained by a first reaction for 10 hours;
[0074] Among them, NaNi 0.33 Fe 0.33 Mn 0.33 The mass ratio of O2 sodium ion positive electrode material to BaCl2 additive is 1:0.025, NaNi 0.33 Fe 0.33 Mn 0.33 The mass ratio of O2 sodium ion positive electrode material, polyacrylic acid and acetylene black is 8:1:1.
[0075] The TEM image of the sodium ion positive electrode material containing the first coating layer prepared in step (1) is as follows: Figure 1 As shown, from Figure 1 It can be seen that the surface of the sodium ion positive electrode material is coated with a layer of organic material.
[0076] The schematic diagram of the structure of the sodium ion positive electrode material in the prepared positive electrode slurry is as follows Figure 2 As shown, wherein 1-the second coating layer, 2-the first coating layer, 3-the sodium ion positive electrode material core, Figure 2 It can be seen that the generated precipitation protective layer is evenly and densely coated on the surface of the material.
[0077] (a) TEM Mapping schematic diagram and (b) linear scan of the prepared sodium ion cathode material Figure 3 As shown, from Figure 3It can be seen that the generated precipitation protective layer is evenly and densely coated on the surface of the material.
[0078] The long cycle stability of the prepared sodium ion cathode material is as follows Figure 4 As shown, from Figure 4 It can be seen that the sodium ion positive electrode material prepared by the aqueous homogenization system is stable in the aqueous phase, and the sodium ion battery has excellent long cycle performance, which is comparable to the performance of the oil-based homogenization process and secondary batteries.
[0079] Example 2
[0080] This embodiment provides a sodium ion positive electrode material and a method for preparing a sodium ion positive electrode slurry, the preparation method comprising the following steps:
[0081] (1) Mix sodium vanadium phosphate (Na3V2(PO4)3 material (commercially available), 1,3,5-naphthalenetrisulfonic acid, and tetrahydrofuran (THF) solvent, stir and dissolve, and heat in a water bath at 70°C for 6 hours to deposit the organic material on the surface of the sodium ion positive electrode material to form a first coating layer. After heating is completed and cooled to room temperature, the mixed solution is filtered, and the obtained solid matter is washed three times with THF solvent and dried to obtain sodium vanadium phosphate (Na3V2(PO4)3 sodium ion positive electrode material containing the first coating layer; wherein NaNi 0.33 Fe 0.33 Mn 0.33 The mass ratio of O2 positive electrode material and 1,3,5-naphthalenetrisulfonic acid is 1:0.5.
[0082] (2) Mixed NaNi containing the first coating layer 0.33 Fe 0.33 Mn 0.33 O2 sodium ion positive electrode material, sodium polymethacrylate, conductive graphite, CaCl2 additive and water, and the positive electrode slurry is obtained by a first reaction for 10 hours;
[0083] Among them, NaNi 0.33 Fe 0.33 Mn 0.33 The mass ratio of O2 sodium ion positive electrode material to CaCl2 additive is 1:0.2, NaNi 0.33 Fe 0.33 Mn 0.33 The mass ratio of O2 sodium ion positive electrode material, sodium polymethacrylate and conductive graphite is 8:1:1.
[0084] Example 3
[0085] This embodiment provides a sodium ion positive electrode material and a method for preparing a sodium ion positive electrode slurry, the preparation method comprising the following steps:
[0086] (1) 1,4-Benzene diphosphonic acid is placed in a culture dish, and sodium iron phosphate NaFePO4 positive electrode material (commercially available) is suspended in an upper container. The culture dish is heated at 120°C for 6 hours to allow 1,4-Benzene diphosphonic acid to volatilize and spontaneously grow on the surface of the positive electrode material to form a coating layer. After cooling to room temperature, the internal powder is stirred, and then heating, cooling, and stirring are repeated 4 times to obtain a sodium iron phosphate NaFePO4 sodium ion positive electrode material containing a first coating layer.
[0087] (2) Mixed NaNi containing the first coating layer 0.33 Fe 0.33 Mn 0.33 O2 sodium ion positive electrode material, sodium alginate, carbon nanotubes, ZnCl2 additive and water, and the positive electrode slurry is obtained by a first reaction for 10 hours;
[0088] Among them, NaNi 0.33 Fe 0.33 Mn 0.33 The mass ratio of O2 sodium ion positive electrode material to ZnCl2 additive is 1:0.3, NaNi 0.33 Fe 0.33 Mn 0.33 The mass ratio of O2 sodium ion positive electrode material, sodium alginate and carbon nanotubes is 8:1:1.
[0089] Example 4
[0090] This embodiment provides a method for preparing a sodium ion positive electrode slurry, which is different from Embodiment 1 only in that the mass ratio of the sodium ion positive electrode material and the water-soluble salt additive in the first coating layer in step (2) is 1:0.005.
[0091] Example 5
[0092] This embodiment provides a method for preparing a sodium ion positive electrode slurry, which is different from Embodiment 1 only in that the mass ratio of the sodium ion positive electrode material and the water-soluble salt additive in the first coating layer in step (2) is 1:0.5.
[0093] Example 6
[0094] This embodiment provides a method for preparing a sodium ion positive electrode slurry, which is different from Embodiment 1 only in that the mass ratio of the sodium ion positive electrode material to the organic material in step (1) is 1:0.05.
[0095] Example 7
[0096] This embodiment provides a method for preparing a sodium ion positive electrode slurry, which is different from Embodiment 1 only in that the mass ratio of the sodium ion positive electrode material to the organic material in step (1) is 1:1.5.
[0097] Comparative Example 1
[0098] This comparative example provides a method for preparing a sodium ion positive electrode slurry, which is different from Example 1 only in that, when preparing the sodium ion positive electrode slurry, step (2) adopts an oil-based reaction system, and the solvent water is replaced by an equal amount of N-methylpyrrolidone.
[0099] Comparative Example 2
[0100] This comparative example provides a method for preparing a sodium ion positive electrode slurry, which is different from Example 1 only in that when preparing the sodium ion positive electrode slurry, no water-soluble salt additive is added in step (2).
[0101] Comparative Example 3
[0102] This comparative example provides a method for preparing a sodium ion positive electrode slurry, which is different from Example 1 only in that, when preparing the sodium ion positive electrode slurry, no organic material is added in step (1).
[0103] Test method: The positive electrode slurries prepared in Examples 1 to 7 and Comparative Examples 1 to 3 were coated on the current collectors respectively and dried under vacuum at 105°C for 5 hours. The pole pieces were rolled with a roller press at a pressure of 10 MPa to reduce the thickness of the pole pieces from 60 μm before rolling to 30 μm after rolling. The compaction density after rolling was 3.0 g·cm -3 , and then punch the electrode into a 12mm positive electrode.
[0104] A CR2032 button-type battery was assembled in an argon-filled glove box using a sodium sheet with a diameter of 16 mm as the negative electrode, a glass fiber separator Grade GF / A as the separator, and NaClO4 (PC=100 Vol%, 3% FEC) as the electrolyte.
[0105] Test standard: At a constant temperature of 26°C, the button cell was subjected to a constant current discharge test using a Xinwei electrochemical workstation. The voltage range was 2.0-4.0V, 3 cycles of pre-activation were performed at a current density of 0.1C, and then a long cycle test was performed at a current density of 1C.
[0106] Table 1
[0107] <![CDATA[Initial discharge capacity / mAh·g -1 > Capacity retention rate after 100 cycles / % Example 1 119 95.1 Example 2 115 95.9 Example 3 112 96.9 Example 4 33 97.0 Example 5 100 90.1 Example 6 28 97.5 Example 7 98 89.9 Comparative Example 1 120 82.2 Comparative Example 2 62 87.6 Comparative Example 3 25 96.9
[0108] The test results show that:
[0109] (1) It can be seen from Examples 1 to 3 that the present invention provides an aqueous homogenization method, which can greatly reduce environmental pollution and reduce costs by using cheap, non-toxic, and pollution-free water as a solvent. Water is used as a solvent in the homogenization process to reduce production costs. At the same time, by adding a water-soluble salt additive to the slurry, the water-soluble salt additive and the organic material in the sodium ion positive electrode material containing the first coating layer spontaneously undergo a double decomposition reaction, and a precipitation protective layer - an artificial solid electrolyte interface layer (CEI) is generated on the surface of the sodium ion positive electrode material, which not only ensures the stability of the sodium ion positive electrode material to water, but also improves the ionic conductivity of the coating layer, maintains the structural stability of the sodium ion positive electrode material during long-term circulation, and improves the service life of the sodium ion battery.
[0110] (2) By comparing Example 1 with Example 4-Example 5, it can be seen that the present invention further controls the mass ratio of the sodium ion positive electrode material and the water-soluble salt additive in the first coating layer to 1: (0.01-0.1) to ensure that a complete precipitation protection layer is formed on the surface of the first coating layer of the sodium ion positive electrode material. While ensuring the water stability of the positive electrode material, it can have a higher ionic conductivity. The additive content will have a significant effect on the electrochemical performance of the electrode after subsequent water slurry. When the additive content is too little, the generated precipitation layer cannot completely cover the surface of the positive electrode material. The hydrophobic performance of the precipitate is greatly reduced, resulting in the gram capacity of the electrode being significantly lower than that of the oil slurry; when the additive content is too much, the precipitation layer is too thick, which will also affect the electrode during the cycle. + The migration of the electrolyte results in the gram capacity and rate performance being significantly lower than that of the oil-based stirred slurry electrode.
[0111] (3) By comparing Example 1 with Example 6-Example 7, it can be seen that the present invention further controls the mass ratio of the sodium ion positive electrode material to the organic material to be 1: (0.1-1) to achieve the integrity of the first coating layer to achieve the auxiliary hydrophobic effect. If the mass of the organic material is too small, the organic molecule coating is uneven and dense, resulting in poor stability of the positive electrode material in the aqueous phase, and ultimately resulting in the gram capacity of the electrode being lower than that of the oil-based homogenous electrode; if the mass of the organic material is too large, the organic molecule coating layer is too thick, affecting the Na + The embedding / detachment of the electrode leads to the rate performance and gram capacity being lower than that of the oil-based homogenous electrode.
[0112] (4) By comparing Example 1 with Comparative Example 1, Figure 4 It can be seen that the long cycle performance of the secondary battery prepared by the water-based homogenization method of the present invention is better than the long cycle stability of the sodium ion battery prepared by the oil-based mixing method.
[0113] (5) It can be seen from Example 1 and Comparative Example 2 that when no water-soluble salt additive is added during the aqueous homogenization process, a precipitation protective layer is formed, resulting in a low ionic conductivity on the surface of the positive electrode material, which is not conducive to the battery capacity.
[0114] (6) It can be seen from Example 1 and Comparative Example 3 that when no organic material is added during the aqueous homogenization process, the sodium ion positive electrode material is not effectively protected, the water environment corrodes the sodium ion battery positive electrode material, and the active sodium ions inside the material are continuously released, thereby causing serious distortion of the internal structure of the material and rapid decay of the battery capacity. It can be seen from Comparative Examples 2 and 3 that the first coating layer and the second coating layer in the present invention cooperate with each other to protect the positive electrode material from being corroded by water while ensuring the cyclic stability of the sodium ion positive electrode material. Both are indispensable, thereby realizing a method for aqueous homogenization of the sodium ion positive electrode material.
[0115] In summary, the present invention provides an aqueous homogenization method, which can greatly reduce environmental pollution and reduce costs by using cheap, non-toxic and pollution-free water as a solvent. Water is used as a solvent in the homogenization process to reduce production costs. At the same time, by adding a water-soluble salt additive to the slurry, the water-soluble salt additive and the organic material in the sodium ion positive electrode material containing the first coating layer spontaneously undergo a double decomposition reaction, and a precipitation protective layer - an artificial solid electrolyte interface layer (CEI) is generated on the surface of the sodium ion positive electrode material, which not only ensures the stability of the sodium ion positive electrode material to water, but also can improve the ionic conductivity of the coating layer, maintain the structural stability of the sodium ion positive electrode material during long-term circulation, and improve the service life of the sodium ion battery.
[0116] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A sodium ion positive electrode material, characterized in that: The sodium ion positive electrode material comprises a sodium ion positive electrode material core, a first coating layer coated on the surface of the sodium ion positive electrode material core, and a second coating layer coated outside the first coating layer; The raw material of the first coating layer includes an organic material having a hydrophobic molecular skeleton and at least two anionic head groups; The second coating layer includes a precipitation product of a reaction between an anionic head group in an organic material and a water-soluble salt.
2. The sodium ion positive electrode material according to claim 1, characterized in that The thickness of the first coating layer is 2nm-10nm; Preferably, the thickness of the second coating layer is 2nm-10nm.
3. The sodium ion positive electrode material according to claim 1 or 2, characterized in that The organic material includes any one of 1,5-naphthalene disulfonic acid, 1,3,5-naphthalene trisulfonic acid, 1,3,6-naphthalene trisulfonic acid, 1,3,7-naphthalene trisulfonic acid, 1,3,6,8-pyrene tetrasulfonic acid, 1,4-benzenediphosphonic acid, 1,4-butane disulfonic acid, 12-mercapto dodecyl phosphoric acid, 1,5-pentane diphosphoric acid or 1,12-dodecane diphosphoric acid, or a combination of at least two thereof; Preferably, the precipitation product in the second coating layer comprises any one of a barium-containing salt, a magnesium-containing salt, a calcium-containing salt or a zinc-containing salt, or a combination of at least two thereof.
4. A method for preparing a sodium ion positive electrode material according to any one of claims 1 to 3, characterized in that: The preparation method of the sodium ion positive electrode material comprises the following steps: Coating an organic material on the surface of a sodium ion positive electrode material by a liquid phase method and / or a gas phase method to prepare a sodium ion positive electrode material containing a first coating layer; The sodium ion positive electrode material containing the first coating layer, a water-soluble salt additive and water are mixed, and the sodium ion positive electrode material is obtained through reaction and separation.
5. A positive electrode slurry, characterized in that: The positive electrode slurry comprises the sodium ion positive electrode material as described in any one of claims 1 to 3.
6. A method for preparing a positive electrode slurry as claimed in claim 5, characterized in that: The preparation method comprises the following steps: Coating an organic material on the surface of a sodium ion positive electrode material by a liquid phase method and / or a gas phase method to prepare a sodium ion positive electrode material containing a first coating layer; The sodium ion positive electrode material containing the first coating layer, the conductive agent, the binder, the water-soluble salt additive and water are mixed and the positive electrode slurry is obtained through a first reaction.
7. The method for preparing the positive electrode slurry according to claim 6, characterized in that: The binder is a water-soluble binder; Preferably, the mass ratio of the sodium ion positive electrode material and the water-soluble salt additive of the first coating layer is 1:(0.01-0.3); Preferably, the water-soluble salt additive includes any one of soluble barium salt, soluble magnesium salt, soluble calcium salt or soluble zinc salt, or a combination of at least two thereof.
8. The preparation method according to claim 4 or 6, characterized in that: The steps of the liquid phase method include: mixing a sodium ion positive electrode material, an organic material and a first solvent, and performing a second reaction to obtain a sodium ion positive electrode material containing a first coating layer; Preferably, the mass ratio of the sodium ion positive electrode material to the organic material is 1:(0.1-1); Preferably, the first solvent comprises any one of tetrahydrofuran, ethanol or acetone, or a combination of at least two thereof; Preferably, the second reaction further includes solid-liquid separation, washing and drying; Preferably, the gas phase method comprises: heating the organic material to deposit the volatilized organic material on the surface of the sodium ion positive electrode material to form a first coating layer, repeating the deposition and coating 2 to 4 times to obtain the sodium ion positive electrode material containing the first coating layer; Preferably, the heating temperature is 100°C-150°C; Preferably, the heating time is 4h-8h.
9. A positive electrode sheet, characterized in that: The positive electrode sheet is prepared using the positive electrode slurry as claimed in claim 5.
10. A secondary battery, characterized in that: The secondary battery comprises the positive electrode sheet as claimed in claim 9.
Citation Information
Patent Citations
High-specific-capacitance manganese-dioxide conducting polymer composite electrode material with core-shell structure and manufacturing method thereof
CN103151179A
Sodium ion positive electrode material, preparation method thereof and secondary battery
CN118431454A
Corrosion resistant, electrically conductive coated material, and its production method
JP2008121087A
Coated particles, injection material and packing method
US20160215206A1
Cited By
Single-crystal layered sodium ion positive electrode material and preparation method thereof
CN121506935A